2023
DOI: 10.2174/1573397119666230414103624
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Gastroesophageal Reflux Disease Among Patients With Rheumatoid Arthritis: A Systematic Review and Meta-analysis

Abstract: Objective: This study was conducted to determine the association between gastroesophageal reflux disease (GERD) and rheumatoid arthritis (RA) by pooling the evidence from all available studies Methods: Potentially eligible studies were identified from MEDLINE and EMBASE database from inception to April 2021 employing a search strategy that consisted of terms for “Rheumatoid Arthritis” and “Gastroesophageal Reflux Disease”. Eligible studies for the meta-analysis were recruited with conditions of being cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Coincidentally, the HR (1.49) of RA in patients with GERD calculated by one cohort study was approximate to our UVMR result, but the HR (1.46) of GERD in patients with RA is not found in our study ( Kim et al, 2021 ). Recently, a meta-analysis research based on cohort studies has also reported an OR of 1.98 for GERD in patients with RA ( Thongpiya et al, 2023 ). It is important to note that the observational studies utilized in the meta-analysis were predominantly conducted on the Asian population, whereas our MR analysis is based on the European population.…”
Section: Discussionmentioning
confidence: 99%
“…Coincidentally, the HR (1.49) of RA in patients with GERD calculated by one cohort study was approximate to our UVMR result, but the HR (1.46) of GERD in patients with RA is not found in our study ( Kim et al, 2021 ). Recently, a meta-analysis research based on cohort studies has also reported an OR of 1.98 for GERD in patients with RA ( Thongpiya et al, 2023 ). It is important to note that the observational studies utilized in the meta-analysis were predominantly conducted on the Asian population, whereas our MR analysis is based on the European population.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Italian pizza is easier to digest, because high-quality tomato sauce is generally used [77], and the pizza is cooked at scorching temperatures [78]. This is a point in favor of pizza consumption in RA patients, who show an increased prevalence of gastro-esophageal reflux [79]. (3) In Italian pizza, not only does the emulsion of oil with tomato sauce before the cooking phase contribute to the uniform cooking of the ingredients [28], but it generally enhances the pizza's antioxidant potential, including the content of phenolic compounds and lycopene, the Trolox Equivalent Antioxidant Capacity, and the bio-accessibility of phenolic compounds and lycopene [77].…”
Section: Discussionmentioning
confidence: 99%